DETERMINATION OF THE SPORTS PRODUCTS CONSUMER PROFILES OF THE TURKISH ARMED FORCES PERSONNEL (Journal of Pharmaceutical Negative Results, 2022)
This study was carried out in order to determine the sports consumer profile of the officers, non-commissioned officers and specialist sergeants from the Turkish Armed Forces in the Istanbul garrison.114 military personnel voluntarily participated in the study. Polatcan (2020), in his doctoral study, revealed 31 items in the consumer profiling study, with a 5-point Likert scale (Strongly Disagree, Disagree, Undecided, Agree, Totally Agree) and 5 sub-dimensions (Socialization, Brand, Entertainment, Participation and Media). “Sports Consumer Scale” was used. Since the distributions were normal, One Way ANOVA, Independent T test and multiple correlation analysis were used as parametric tests. No significant difference was found according to the factors affecting the sports consumption of military personnel according to age, monthly income, place of being affected in purchasing and regular sports. However, significant differences were found in the entertainment factor affecting sports consumption according to TAF status, and the difference showed that it was due to the specialist sergeants. In addition, significant differences were found in the participation factor that affects sports consumption according to the purchasing factor. The difference arises from those who buy from the store. Differences were observed between the participation factor in sports consumption and it was determined that the scores of those who do not use credit cards are also higher than those who use them.As a result, there is a negative correlation between the age (r=-.22) of the entertainment factor affecting the sports consumption of military personnel and a low level of positive correlation (r=.21) with the TAF status. There is a low-level positive relationship between purchasing imitations of sports products brands and socialization (r=.19), and a moderately positive relationship between the brand sub-dimension (r=.45). There is a negative correlation between the use of a credit card while purchasing sports products and the participation sub-dimension (r=-.19).